Omnichannel Marketing Strategy and Competitive Advantage in Mediating Market Orientation toward Marketing Performance - Gunawan, Detia; Ramdan, Asep Muhamad; Jhoansyah , Dicky (JURNAL MANAJEMEN MOTIVASI, 2026)
This study aims to analyze the effect of market orientation on marketing performance with omnichannel marketing strategy and competitive advantage as mediating variables in food-sector MSMEs in Sukabumi City. The method used is a quantitative approach with a survey of 120 respondents and data analysis using SEM-PLS. The results show that market orientation significantly influences omnichannel strategy and competitive advantage. Both variables mediate the relationship between market orientation and marketing performance. The implication of this study suggests that market orientation, supported by omnichannel strategy and competitive advantage, can optimally enhance the marketing performance of MSMEs.